Bridging the Gap Between Geographical Information Systems and Planetary Virtual Observatory. Issue 3 (5th March 2019) - Minin, M.; Rossi, A. P.; Marco Figuera, R.; Unnithan, V.; Marmo, C.; Walter, S. H. G.; Demleitner, M.; Le Sidaner, P.; Cecconi, B.; Erard, S.; Hare, T. M.
Abstract : Virtual Observatory tools are specifically designed for astronomical data, but they can be adapted to work with geospatial data by providing existing Geographical Information System tools with Simple Application Messaging Protocol interface. Open source QGIS package was chosen as a platform for this. The Simple Application Messaging Protocol interface was made with Python plug‐ins. Geospatial data were exposed to Virtual European Solar and Planetary Access via a dedicated German Astronomical Virtual Observatory Data Center Helper Suite server and several tables exposing existing Open Geospatial Consortium—compliant planetary services were published to Virtual European Solar and Planetary Access providing a variety of geospatial data types: vector data and spectral cube rasters, as well as Open Geospatial Consortium Web Map Service of planetary maps. Plain Language Summary: Geospatial Science and Astronomy are closely related fields which nevertheless use different tools, standards, interfaces, formats, and protocols. Heterogeneous Astronomical data are accessed routinely via standard system largely known as Virtual Observatory, whereas in Planetary Science, capabilities of cross‐mission and cross‐archive data discovery are lacking. The present work tries to bridge these two communities by leveraging on commonalities in data types and tools while exposing Geospatial data sets to the Virtual Observatory and creating necessary interfaces in Geographical Information Systems. Key Points: Geospatial data sets were exposed to Virtual Observatory QGIS plug‐ins interface to Virtual Observatory was developed